“NEW FORMS OF IDENTITY POLITICS IN KARNATAKA: THE ROLE OF SOCIAL MEDIA AND DIGITAL PLATFORMS.” (International Journal of Food and Nutritional Sciences, 2022)
This essay examines the ways in which digital platforms and social media have sparked new identity politics movements in Karnataka, India. Karnataka's identity battles, which have historically been based on caste, language, and regionalism, have developed into vibrant, tech-driven movements. Political engagement has become more democratic because to platforms like Facebook, Twitter, WhatsApp, and YouTube, which allow underrepresented groups to speak up while also dividing popular opinion. In order to demonstrate how digital tools increase both empowerment and polarization, the paper examines instances including the Hijab controversy, Lingayat religious identity movements, and Cauvery River disputes. Through disinformation, echo chambers, and algorithmic biases, social media has exacerbated divisions even as it has promoted unity among Dalits, minorities, and regional linguists. The article assesses Karnataka's policy responses to digital issues, such as content management and IT legislation. It makes the case that unmanaged platform dynamics endanger social cohesiveness even as digital activism redefines political agency. The paper highlights the complex nature of Karnataka's digital identity politics by fusing historical background with current case studies. It also advocates for inclusive governance frameworks to reduce risks and maximize chances for democratic participation.